AGROECOLOGICAL EFFICIENCY OF SEWAGE SLUDGE AND VERMICOMPOST IN AGROCENOSES OF CULTIVATED OAT - Tatyana V. Khabarova; Dmitriy V. Vinogradov; Boris I. Kochurov; Viktor I. Levin; Nikolay V. Byshov (Юг России: экология, развитие, 2018)
Aim. The article suggests research on biotransformation of sewage sludge from treatment facilities in the city of Ryazan into organomineral fertilizer. An ecological analysis of the efficiency of fertilizer use in oat cultivation is proposed. Methods. Determination of growth and development indices of plants, structure of the oats crop of the Skakun variety, agrochemical indices of the soil. Results. Analyzed the effect of sewage sludge and vermicomposts, which are the basis for the cultivation of oats (Avena sativa) on organic soils (peat-mineral soil) which forms favorable conditions for the development of plants and the formation of high productivity of the crop, ensuring the production of ecologically safe grain products. Conclusion. The effect of the dehydrated sewage sludge and vermicomposts from the biological treatment plant in the city of Ryazan on the productivity of the Skakun oat has been revealed. The use of sewage sludge and vermicomposts is marked by an increase in the elements of the crop structure of the grain crop, as a consequence, by an increase in the bioproductivity of the phytocenosis, which indicates the advisability of using sewage sludge as a fertilizer.